SISTEM PAKAR MENDIAGNOSA PENYAKIT FLU BURUNG SECARA ONLINE DENGAN METODE FORWARD CHAINING - Arif Kurniawan (Jurnal Informatika, 2018)
An expert system can be defined as a computer software that has a knowledge base for a particular domain and uses inference reasoning resembling an expert in solving a problem. Expert System to diagnose bird flu disease to discuss about how to create an expert system application that if able to diagnose bird flu disease and provide solutions of the disease. Where the expert system when associated with the ability of doctors in the early mediagnosa patient health conditions, can be created a computer system that is tasked to know and analyze the symptoms of illness suffered by patients to then provide direct advice to these patients. Inference technique that is done is forward tracking (forward chaining) with the method of search (Best First Search).